Alpha-2 agonists for refractory neurological symptoms in pediatric palliative care: a scoping review - Salerno, Annalisa; Baratiri, Fernando; La Piana, Chiara; Bincoletto, Angelica; Benini, Franca; Zanin, Anna (Frontiers in Pediatrics, 2025)
BackgroundChildren receiving palliative care often suffer from refractory neurological symptoms. In recent years, there has been a growing interest in the use of alpha-2 agonists as a second- or third-line therapy for severe dystonia and irritability.ObjectivesThe aim of this review was to provide an overview of the scientific literature on the use of alpha-2 agonists for the treatment of refractory neurological symptoms in pediatric palliative care, evaluating the evidence available and identifying gaps related to their reported efficacy and safety.MethodsA scoping review was performed according to the PRISMA extension. A systematic search was conducted in PubMed, Medline, EMBASE, Web of Science, CINAHL, and The Cochrane Library, using terms referring to alpha-2 agonists and neurological symptoms in pediatric palliative care.ResultsSeven articles were identified, including three case reports, two case series, one observational cohort study, and one retrospective analysis. Two drugs (dexmedetomidine, n = 4/7, and clonidine, n = 3/7) were investigated, encompassing a total of 44 patients aged between 7 months and 18 years. Most patients (95%) initiated treatment in an inpatient setting before transitioning to home care. All patients reported clinical improvement; however, 25% of children treated with clonidine discontinued its use due to ineffectiveness or side effects. No adverse effects were reported with dexmedetomidine use.ConclusionAlpha-2 agonists are increasingly being used to manage intractable neurological symptoms in pediatric palliative care. However, evidence regarding their safety profile and effectiveness remains limited, highlighting the need for further research in this area.